2012
DOI: 10.1016/s0924-9338(12)75200-8
|View full text |Cite
|
Sign up to set email alerts
|

P-1033 - Serum S100B levels in first-episode psychosis and juvenile myoclonic epilepsy

Abstract: Introduction: S100B is a 21 kDa protein expressed primarily in astrocytes and has been related with brain dysfunction. There is evidence for increased S100B in schizophrenia, including first-episode psychosis (FEP), and in epilepsy specially after seizures. Pico and nanomolar levels of S100B are neurotrophic and micromolar levels are toxic and apoptotic. Objective: To assess serum levels of S100B at admission and at discharge in a patient with FEP who had comorbid juvenile myoclonic epilepsy (JME). Methods and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Twenty-two records were identified for full-text analysis. We scrutinized these records and excluded four due to a lack of necessary data (Yelmo et al, 2012; Chen et al, 2015), because the results were also reported in other publications (Lu, 2010; Chen, 2011a). Ultimately, 18 studies encompassing 1,057 cases and 821 controls met the criteria for inclusion in our meta-analysis (Figure 1) (Portela et al, 2003; Li et al, 2004; Yun, 2009; Lu et al, 2010; Chen, 2011b; Liu et al, 2011; Atici et al, 2012; Mikkonen et al, 2012; Shiihara et al, 2012; Wang and Han, 2012; Xu et al, 2012; Yuan et al, 2014; Yun et al, 2015; Wang et al, 2016, 2018; Hao et al, 2017; Zhao et al, 2017; Zhang et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Twenty-two records were identified for full-text analysis. We scrutinized these records and excluded four due to a lack of necessary data (Yelmo et al, 2012; Chen et al, 2015), because the results were also reported in other publications (Lu, 2010; Chen, 2011a). Ultimately, 18 studies encompassing 1,057 cases and 821 controls met the criteria for inclusion in our meta-analysis (Figure 1) (Portela et al, 2003; Li et al, 2004; Yun, 2009; Lu et al, 2010; Chen, 2011b; Liu et al, 2011; Atici et al, 2012; Mikkonen et al, 2012; Shiihara et al, 2012; Wang and Han, 2012; Xu et al, 2012; Yuan et al, 2014; Yun et al, 2015; Wang et al, 2016, 2018; Hao et al, 2017; Zhao et al, 2017; Zhang et al, 2018).…”
Section: Resultsmentioning
confidence: 99%